VALUE ORIENTATIONS OF A PERSON IN THE CONTEXT OF PERCEPTION OF THE OTHER - Vatyan, Tatevik (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
The rapid development of modern societies, the multi-layered nature of intercultural relations, as well as immigration and emigration processes, demonstrate the need to study and shed new light on the perception of the other in psychological science. Over time, the ideas about the other have undergone some changes; therefore, a multi-faceted analysis of the perceptions of the other in modern society is important. This article examines the value orientations of a person in the modern Armenian environment, which are formed in the context of the perception of the other. Theoretical models of value orientations have been analyzed, and modern manifestations of orientations have been subjected to comparative analysis with the ideas about the psychological sovereignty of a person. As a result of qualitative and quantitative analysis, it has become possible to reveal the complex of dichotomous notions of "self-the other", which has been studied among modern Armenian youth.